P-102 A comparison of user feedback in the use of two independently completed advance care directives. (1st September 2015) - Cairney, H; Billings, S; Kinsella, C; Austin, N; Hunter, P
Abstract : Background: In Australia, patient-based Advanced Care Directives (ACDs) have been used in the clinical setting to assist in Advance Care Planning under the guidance of expert medical advice. More recently, person-based ACDs have been developed with the intention that these can be independently completed by people in the community. Aim: To compare feedback, usefulness and the level of assistance required by users completing a patient or person based ACD. Methods: 60 consumers were recruited and randomly allocated to complete one of two ACDs. These ACDs were provided to the consumer's, SDM and a doctor (unknown to consumer). Feedback was obtained from all groups. Results: The majority of users reported the directives were easy to understand, logical and with sufficient space to write answers, regardless of directive type. The majority (93%) of consumers felt they could complete the directive independently. The majority of SDMs felt both directives were helpful with the decision making process. Doctors expressed a preference for the person-based ACD however the majority (92%) reported that either directive type would assist in making treatment decisions. Improvement suggestions by consumers and SDMs related to the inclusion of more examples and definition of terms. Discussion/Conclusion: Consumers and SDMs were positive in regard to the use of ACDs and the ability to complete them independently regardless of the directive type. Whilst doctors showed some preference for the person-based ACD, their greatest support was for people's values and preferences being documented and shared regardless of the type of directive it was written on.